Pharm Adv 2021
DOI: 10.36118/pharmadvances.2021.06
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological basis of the curcumin nutraceutical uses: an update

Abstract: Curcumin is the major phytoconstituent found in the rhizomes of Curcuma longa L. Preparations derived from the rhizome of the plant, referred as turmeric, have been used for centuries in the traditional Indian system of medicine. The recent literature has shown curcumin as one of the most interesting pleiotropic nutraceuticals capable of interacting with different molecular targets involved in chronic diseases. The present review summarizes and critically discusses the very recent literature published between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 276 publications
(344 reference statements)
0
19
0
Order By: Relevance
“…3-5%), and THC being the major metabolite of curcumin [7]. We measured the plasma levels of CUR, DMC, BDMC, and THC which are known to be responsible for the diverse bioactivity of curcuminoids [8,[24][25][26][27] and represented the data for total curcuminoids. Our study results showed that the plasma concentrations of total curcuminoids and its bioavailability were significantly higher for both doses (250 and 500 mg) of CU?…”
Section: Discussionmentioning
confidence: 99%
“…3-5%), and THC being the major metabolite of curcumin [7]. We measured the plasma levels of CUR, DMC, BDMC, and THC which are known to be responsible for the diverse bioactivity of curcuminoids [8,[24][25][26][27] and represented the data for total curcuminoids. Our study results showed that the plasma concentrations of total curcuminoids and its bioavailability were significantly higher for both doses (250 and 500 mg) of CU?…”
Section: Discussionmentioning
confidence: 99%
“…The curcumin concentration is critical for evaluating the biological consequences of frequent oral intake. Bio-transformed moieties, such as tetra hexahydro–curcumin, have drawn attention because of their poor systemic bioavailability [ 87 ].…”
Section: Phytomedicine Drug Delivery Using Nanoparticlesmentioning
confidence: 99%
“…Curcumin is a well-known curcuminoid extracted from the rhizome of Curcuma longa . Various biological activities of curcumin have been described in the literature including antioxidant, antimicrobial, and anti-inflammatory properties [ 12 ]. Zoi V. et al [ 13 ] explored the possible use of curcumin as a radio-sensitizing agent in the treatment of glioblastoma, the most common and severe malignant brain tumor.…”
Section: Recent Advances In the Role Of Polyphenols In Inflammatory Conditionsmentioning
confidence: 99%